Organic Photocathode Supported by Copper Nanosheets Array for Overall Water Splitting. Issue 6 (22nd December 2021) - Zhang, Rui; Sun, Xingjun; Zheng, Lingcheng; Diao, Lingxue; Chen, Feifei; Li, Yan; Wang, Shuli; Wang, Yajiang; Wang, Weihua; Lu, Feng; Dong, Hong; Liu, Hui; et al.
Abstract: The Z‐scheme overall solar water splitting is a mimic of natural photosynthesis to convert solar energy into chemical energy. Since the energy levels of most organic semiconductors match well with the hydrogen evolution potential, they have great application prospects as photocathodes in Z‐scheme photoelectrochemical systems. However, due to the weak light absorption and difficult carrier separation, the photocurrent density and onset potential of organic photocathodes are still low. To solve these problems, we introduced a copper nanosheets array (Cu NSA) framework under organic layers to increase the surface reaction sites, improve the light absorption and enhance the distribution range of built‐in electric field simultaneously. As a result, the photocurrent density and onset potential of poly(3‐hexylthiophene) : [6, 6]‐phenyl‐C61 ‐butyric acid (P3HT : PCBM) photocathode were enhanced significantly. The onset potential increased by 50 mV to 0.65 V vs. RHE, and the photocurrent density reached −1 mA cm −2 at 0 V vs. RHE, which was 18 times that of the sample without Cu NSA. The optimized photocathode was connected with titanium dioxide nanorods array photoanode in a tandem manner to realize the spontaneous overall water splitting. Without bias and co‐catalyst, the photocurrent density was maintained at 110 μA cm −2 and the solar‐to‐fuel conversion efficiency was 0.14 % in neutral solution. These results provide a feasible method for optimizing the performance of organic photocathodes. Abstract : A simple Cu nanosheets array support structure was provided as the substrate of organic photocathode, which provides more reactive sites and increases the effective light absorption area. Furthermore, the introduction of Cu NSA increases the distribution range of the built‐in electric field, thus improving the separation efficiency of photogenerated carriers and the photocatalytic performance. The proposal of the simple support structure provides a direction for the design and implementation of spatially separated PEC cell.